Inequality and the GB2 income distribution - Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2007)
The generalized entropy class of inequality indices is derived for Generalized Beta of the Second Kind (GB2) income distributions, thereby providing a full range of top-sensitive and bottom-sensitive measures. An examination of British income inequality in 1994/95 and 2004/05 illustrates the analysis.
urn:nbn:de:101:1-2008032830
Keywords: 330; Disparitätsmaß; Entropie; Einkommensverteilung; Theorie; Großbritannien